Synthesis and antituberculosis activity of 2-(aryl/alkylamino)-5-(4-aminophenyl)-1,3,4-thiadiazoles and their Schiff bases - (:unkn) unknown (ARKAT USA INC, 2006)
A series of new Schiff bases were synthesized through the condensation reaction of 1,3,4-thiadiazoles containing a aromatic primary amine and 3-hydroxybenzaldehyde, salicylaldehyde, 5-nitrofurfuraldehyde or 3-nitrobenzaldehyde. The synthesized compounds screened for antituberculosis activity against Mycobacterium tuberculosis H(37)Rv using BACTEC 460 radiometric system. Among the tested compounds, 2-phenylamino-5-[4-(2-hydroxybenzylideneamino)phenyl]-1,3,4-thiadiazol (5a) showed the highest inhibitory activity (51%). The activities of the synthesized Schiff bases were compared with those of the starting 2-(aryl/alkylamino)-5-(4-aminophenyl)-1,3,4-thiadiazoles (4a-e). Some Schiff bases showed higher growth inhibition than the starting amines.
Keywords: Schiff bases; 1,3,4-thiadiazoles; antituberculosis activity; synthesis; SUBSTITUTED 1,3,4-THIADIAZOLES; ANTICONVULSANT ACTIVITY; STRUCTURE ELUCIDATION; DERIVATIVES; THIOSEMICARBAZIDES; THIADIAZOLES; AGENTS